Outcome of pregnancy in women 35 years of age and above - Jahan, Mst Khurshida; Shafiquzzaman, M; Nahar, K; Rahman, M; Sultana, N; Rahman, MM; Begum, R (Mymensingh Medical Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Mymensingh Med J. 2009 Jan;18(1):7-12. The abstract of this article is available on the PubMed website